Podcast Media in Consultation Services to Develop Academic Stress Prevention Skills - Purwadi, Purwadi; Handaka, Irvan Budhi; Arikunto, Suharsimi; Prasetiawan, Hardi; Hendiani, Nurlita; Saputra, Rahmat Ponco Adi (Universitas Islam Negeri Raden Intan Lampung, 2021)
The rapid digitization of education in a pandemic has an impact on academic stress conditions. Counsellors have not implemented various innovative media but need relevant and millennial media to support consulting services with podcasts. This article aims to analyze the feasibility of podcast media in consulting services to develop academic stress prevention skills. Research and development limited to five stages help know the feasibility of podcasts as support for consulting services, especially academic stress prevention skills. The data analyzed the feasibility questionnaire instrument through expert validators, media, and practitioners (counsellors) quantitatively with percentages and inter-rater analysis. The results of the research show that podcast media is quite relevant to use in consulting services. The relevance and accuracy of podcast media can adjust to the content of the supporting material. Prevention of academic stress isn’t only with knowledge but skills to cope with academic stress in all conditions, especially in pandemic and post-pandemic situations. Professional and millennial counsellors can develop skills in the use of podcast media in consulting services. Can use Podcast media directly in consulting services. Recordings of podcast results can be used indirectly in consulting services or group guidance services, group counselling, individual counselling, and classical guidance as a follow-up.